Hubungan Tingkat Konsumsi Protein, Zinc, dan Vitamin C dengan Produktivitas Kerja Wanita pada Tenaga Pemetik Teh di PT Duta Agrinti Karanganyar Kabupaten Tegal - Ulwiyah, Nela Alfiyatul; Ulvie, Yuliana Noor Setiawati; Handasari, Erma; Kusuma, Hapsari Sulistya (Jurnal Gizi, 2023)
Tea picking workers are a population who often perform physical activities in a hot environment for a long time so that they have the potential to experience lack of fluids and intake due to excessive sweating or exertion. The low work productivity of each individual is influenced by poor nutritional status and health status. Therefore, efforts to improve the quality of human resources are one of the important things for increasing the work productivity of an employee or employee according to WHO. The purposeof this study was to determine the relationship between the level of consumption of protein, zinc, and vitamin C with work productivity of tea pickers at PT. Duta Agrinti. This type of research is analytical researchwith a cross sectional study design. The sampling technique used the Simple Purposive Sampling method with a sample size of 46 respondents. Data collection of protein, zinc, and vitamin C consumption levelswas obtained from filling out the Recall form 2x24 hours for 2 days not consecutively, and work productivity was obtained from observation sheets of tea pick weighing results. The data normality test used the Kolmogorov-Smirnov test while the relationship test used the Rank Spearman correlation test. There were 93.5% of respondents who picked tea had a weight deficit level of protein consumption, with an average of 75,92% ± 26,89. About 93.5% of respondents who picked tea had a low zinc consumption level, with an average of 53.93% ± 19.29. About 95.7% of respondents who picked tea had a low level of vitamin C consumption, with an average of 22.31% ± 32.13. About 23.9% of respondents who picked tea had low work productivity, with an average of 6.58 kg / hour ± 2.33. There is a relationship between the level of protein consumption and the level of zinc consumption with the work productivity of women who pick tea. There is no correlation between the level of vitamin C consumption and the work productivity of women who pick tea (p=0,177). Keywords: Productivity of Tea Pickers, Protein, Zinc, Vitamin C.